Determination of adhesion of the coating deposited by arc spraying with pulsation of atomizing air flow - Zakharova, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
During electric arc spraying, during the transfer of molten metal by air flow, there is a significant burnout of alloying elements with the formation of a large amount of oxides, which negatively affects the adhesion of the coating to the base. A solution to the problem of increasing the adhesion strength by using pulsation of the atomizing air flow is proposed. At the optimal frequency of the pulsed flow shut-off, the time of formation of liquid metal droplets at the ends of the electrodes coincides with the frequency of pulses of the spraying flow. As a result, the droplets acquire an optimal size, they are transported by an air flow with conservation of energy, a lower mass of oxygen and, as a consequence, a significant decrease in the oxidation of alloying elements in the sprayed material. The existing test methods of sprayed coatings for adhesion strength to the base are analyzed. The design of a modernized device for determining the adhesion strength is developed and described, which provides complex loading of the coating with a combination of tear-off and shear. The tests revealed a significant (up to two times) increase in the adhesion strength of aluminum, zinc-aluminum and steel (Sv08A) coatings applied with air pulsation. This is achieved by increasing the number of fusion zones of the coating particles between themselves and with the base. It is shown that the effect of the pulsation frequency on the adhesion strength changes along a curve with a maximum corresponding to a frequency of 70–80 Hz, regardless of the coating material. It has been established that the aluminum coating has an increased tendency to oxidation, as a result of which it is 15–20 % inferior to the zinc-aluminum coating in adhesion strength. The data obtained substantiate the use of the proposed spraying technology in production